If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 113 = -9x + 50 Reorder the terms: 113 = 50 + -9x Solving 113 = 50 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 113 + 9x = 50 + -9x + 9x Combine like terms: -9x + 9x = 0 113 + 9x = 50 + 0 113 + 9x = 50 Add '-113' to each side of the equation. 113 + -113 + 9x = 50 + -113 Combine like terms: 113 + -113 = 0 0 + 9x = 50 + -113 9x = 50 + -113 Combine like terms: 50 + -113 = -63 9x = -63 Divide each side by '9'. x = -7 Simplifying x = -7
| 8c+3=19 | | 16=3(6x+2)+4(x-3) | | 4(5x+2)=7x-5 | | 29=1-4x | | 5(-16+4y)=40 | | 3(3x-4)-2=3(x-4)+34 | | M-4=-14 | | 4x^4-x^2+6x-9=0 | | 18x-6=10x+18 | | -6+(15)= | | 3x+2x+15=50 | | 7p-6=4+8p-6p | | 40=-2(4-x) | | 1-2-3-4-5=5 | | -1(3-2x)=17 | | 5+6(x-1)=11+5 | | 2x+2=x+15 | | 8(2x+4)-4x=20 | | 38-4x=7x-19 | | 7x+1=4x-17 | | 4x+40=13-5x | | 3(x-6)=20 | | 2x+3x+6=36 | | -3+2x+15=27 | | -52+2x=84+6x | | x^3+6x^2+6x+8=0 | | (3x+12)=5x | | 42=4x+4x-6 | | 4(3x+-5)+6=7(x-2)+6x | | 5x+7-2x+1=17 | | 3x-3+x-7+x=180 | | 4(3x+-5)+6=6x+2(3x-8) |